2020
DOI: 10.3847/1538-4357/ab5f5f
|View full text |Cite
|
Sign up to set email alerts
|

No Significant Evolution of Relations between Black Hole Mass and Galaxy Total Stellar Mass Up to z ∼ 2.5

Abstract: We investigate the cosmic evolution of the ratio between black hole mass (M BH ) and host galaxy total stellar mass (M stellar ) out to z ∼ 2.5 for a sample of 100 X-ray-selected moderate-luminosity, broad-line active galactic nuclei (AGNs) in the Chandra-COSMOS Legacy Survey. By taking advantage of the deep multi-wavelength photometry and spectroscopy in the COSMOS field, we measure in a uniform way the galaxy total stellar mass using a SED decomposition technique and the black hole mass based on broad emissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
112
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 99 publications
16
112
1
Order By: Relevance
“…Our analysis adds key evidence, using IR data, to an increasing body of work (Delvecchio et al 2019;Ding et al 2020;Shankar et al 2020;Suh et al 2020) on the weak evolution in the BHAR/SFR and its relatively low normalization relative to local raw dynamical M BH − M * relations.…”
Section: Relation Between Stellar Mass and Black Hole Masssupporting
confidence: 54%
“…Our analysis adds key evidence, using IR data, to an increasing body of work (Delvecchio et al 2019;Ding et al 2020;Shankar et al 2020;Suh et al 2020) on the weak evolution in the BHAR/SFR and its relatively low normalization relative to local raw dynamical M BH − M * relations.…”
Section: Relation Between Stellar Mass and Black Hole Masssupporting
confidence: 54%
“…2). Moreover, our data points lie close to the fit recently found by Suh et al (2020) by including local plus highz (up to z=2.5) AGN and to the unbiased M BH − M relation computed by Shankar et al (2016), who interpreted the discrepancy between the observed location of quiescient and active galaxies in the M BH − M plane as an observational bias (Shankar et al 2019). Indeed, our newly discovered z ∼ 1.6 AGN have M BH /M ratio consistent with local active galaxies, thus showing no or negligible evolution in the intrinsic M BH − M relation, in agreement with most recent works (Shankar et al 2019;Suh et al 2020).…”
Section: The M Bh − M Planesupporting
confidence: 90%
“…Correlations between central black hole mass and host galaxy total stellar mass for the two broad line AGN discovered in the core of XDCP004 (black circles with errors). As reference, the dashed red line is a linear fit to the sample of Kormendy & Ho (2013, KH13) by Shankar et al (2019), while the solid green line is the fit to local AGN by Reines & Volonteri (2015, RV15) and the short-dashed blu line is the fit by Suh et al (2020) to local + high-z AGN. Finally the solid black line is the de-biased MBH − M relation derived by Shankar et al (2016, S+16) with its scatter (yellow area).…”
Section: Agn and Sf Activitymentioning
confidence: 99%
“…Since the stellar mass evolves much more modestly than the black hole mass [a trend also found in recent AGN observations from the Chandra-COSMOS Legacy Survey; Ref. 15], the central black hole mass makes up a much larger fraction of the stellar mass at high redshifts (a fraction of ∼ 0.3 at redshift z ∼ 6 compared to 10 −4 at z ∼ 0). This fact, whose validity has been hinted at in the past [11,16], is well-supported by the recent ALM A 1 spectroscopic study [10] of [CII]-detected quasars at z > 6 which indicates significantly more than two orders of magnitude evolution of the locally observed black hole -bulge mass relation [7].…”
Section: Introductionmentioning
confidence: 76%